Standardizing default electronic health record tools to improve safety for hospitalized patients with Parkinson’s disease - Wu, Allan D.; Walter, Benjamin L.; Brooks, Anne; Buetow, Emily; Amodeo, Katherine; Richard, Irene; Mundth, Kelly; Azmi, Hooman (Frontiers in Aging Neuroscience, 2024)
Electronic Health Record (EHR) systems are often configured to address challenges and improve patient safety for persons with Parkinson’s disease (PWP). For example, EHR systems can help identify Parkinson’s disease (PD) patients across the hospital by flagging a patient’s diagnosis in their chart, preventing errors in medication and dosing through the use of clinical decision support, and supplementing staff education through care plans that provide step-by-step road maps for disease-based care of a specific patient population. However, most EHR-based solutions are locally developed and, thus, difficult to scale widely or apply uniformly across hospital systems. In 2020, the Parkinson’s Foundation, a national and international leader in PD research, education, and advocacy, and Epic, a leading EHR vendor with more than 35% market share in the United States, launched a partnership to reduce risks to hospitalized PWP using standardized EHR-based solutions. This article discusses that project which included leadership from physician informaticists, movement disorders specialists, hospital quality officers, the Parkinson’s Foundation and members of the Parkinson’s community. We describe the best practice solutions developed through this project. We highlight those that are currently available as standard defaults or options within the Epic EHR, discuss the successes and limitations of these solutions, and consider opportunities for scalability in environments beyond a single EHR vendor. The Parkinson’s Foundation and Epic launched a partnership to develop best practice solutions in the Epic EHR system to improve safety for PWP in the hospital. The goal of the partnership was to create the EHR tools that will have the greatest impact on outcomes for hospitalized PWP.